ESKALASI KOMITMEN INDIVIDU BERDASARKAN LOCUS OF CONTROL DALAM KASUS INVESTASI - Endah Suwarni; Bambang Subroto; Gugus Irianto (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2013)
This study aims to find out whether escalation of commitment at individual who has internal locus of control will be bigger than individual who has external locus of control if getting the negative information and escalation of commitment at individual who has internal locus of control can be mitigated by the information of future benefit of alternative investment. The research was conducted by using experiment approach with investment case that was adapted from experiment designed Ghost (1997). Sixty subjects were participation in experiment is the student at six semester of Accounting Study Program–Politeknik Negeri Malang. Experiment applies 2 x 2 factorial designs. Escalation of commitment variabel is investment decision, whereas internal-external locus of control was measured by using Rotter’s instrument (1966). The hypothesis testing was done by using one-way ANOVA (F-Test) and the treatment effect was tested by using post hoc test with scheffe method. Experiment result expresses that escalation of commitment on individual who has internal locus of control was bigger than individual who has external locus of control, when they got the negative information and escalation of commitment at individual who has internal locus of control can be mitigated by the information of future benefit of alternative investment.